Autonomous differentiation of transgenic cells requiring no external hormone application: the endogenous gene expression and phytohormone behaviors - Sato, Yuka; Minamikawa, Mai F.; Pratama, Berbudi Bintang; Koyama, Shohei; Kojima, Mikiko; Takebayashi, Yumiko; Sakakibara, Hitoshi; Igawa, Tomoko (Frontiers in Plant Science, 2024)
The ectopic overexpression of developmental regulator (DR) genes has been reported to improve the transformation in recalcitrant plant species because of the promotion of cellular differentiation during cell culture processes. In other words, the external plant growth regulator (PGR) application during the tissue and cell culture process is still required in cases utilizing DR genes for plant regeneration.Here, the effect of Arabidopsis BABY BOOM (BBM) and WUSCHEL (WUS) on the differentiation of tobacco transgenic cells was examined. We found that the SRDX fusion to WUS, when co-expressed with the BBM-VP16 fusion gene, significantly influenced the induction of autonomous differentiation under PGR-free culture conditions, with similar effects in some other plant species. Furthermore, to understand the endogenous background underlying cell differentiation toward regeneration, phytohormone and RNA-seq analyses were performed using tobacco leaf explants in which transgenic cells were autonomously differentiating. The levels of active auxins, cytokinins, abscisic acid, and inactive gibberellins increased as cell differentiation proceeded toward organogenesis. Gene Ontology terms related to phytohormones and organogenesis were identified as differentially expressed genes, in addition to those related to polysaccharide and nitrate metabolism. The qRT-PCR four selected genes as DEGs supported the RNA-seq data. This differentiation induction system and the reported phytohormone and transcript profiles provide a foundation for the development of PGRfree tissue cultures of various plant species, facilitating future biotechnological breeding.